1998
DOI: 10.1016/s0005-2736(98)00123-0
|View full text |Cite
|
Sign up to set email alerts
|

P2 receptor-mediated signal transduction in Ehrlich ascites tumor cells

Abstract: The mechanisms, by which the P2 receptor agonists adenosine 5'-triphosphate (ATP) and uridine 5'-triphosphate (UTP) evoke an increase in the free cytosolic calcium concentration ([Ca2+]i) and in intracellular pH (pHi), have been investigated in Ehrlich ascites tumor cells. The increase in [Ca2+]i evoked by ATP or UTP is abolished after depletion of intracellular Ca2+ stores with thapsigargin in Ca2+-free medium, and is inhibited by U73122, an inhibitor of phospholipase C (PLC), indicating that the increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…Thus, ATP also potentiated the RVD response, as shown in rat hepatoma cells [59]. In EATC, we found that ATP stimulated PY receptors [60], which resulted in an increase in [Ca 2+ ] i and activation of charybtotoxin-sensitive K + channels. Figure 11 shows that tyrosine phosphorylation plays a central role in the activation of TASK-2 during cell swelling and RVD.…”
Section: Mechanisms Of Task-2 Activation By Cell Swellingsupporting
confidence: 72%
“…Thus, ATP also potentiated the RVD response, as shown in rat hepatoma cells [59]. In EATC, we found that ATP stimulated PY receptors [60], which resulted in an increase in [Ca 2+ ] i and activation of charybtotoxin-sensitive K + channels. Figure 11 shows that tyrosine phosphorylation plays a central role in the activation of TASK-2 during cell swelling and RVD.…”
Section: Mechanisms Of Task-2 Activation By Cell Swellingsupporting
confidence: 72%
“…The existing literature suggests that P2Y receptor agonists can modulate cell volume in a cell type-specific manner. Thus ATP was found to produce cell shrinkage in hepatocytes and Ehrlich ascites tumor cells (42,56) but swelling in cultured brain astrocytes (52). Although changes in cell volume may be of physiological significance, particularly for renal epithelial cells, which are exposed to frequent cellvolume changes in anisotonic environments, detailed studies on cell-volume dynamics in response to ATP are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Provided the external ATP concentration rises high enough during cell swelling, ATP stimulates the P 2 receptors described in EATC [171], resulting a similar potentiation of the RVD response. …”
Section: Camentioning
confidence: 97%